Effect of Enhanced Fermentation with Aspergillus on the Flavor Quality of Liuyang Douchi, a Traditional Chinese Soybean Product - WU Ziqian, LIU Jingjing, DENG Gaowen, ZHOU Xiao, JIANG Liwen, HU Jialiang, QIN Yeyou, LIU Yang (Shipin Kexue, 2023)
To investigate the effect of enhanced fermentation with different species of Aspergillus on the flavor of Douchi, the quality differences between enhanced fermentation by A. flavus 7214, A. flavus 7622 or A. oryzae and natural fermentation were compared. The results showed that enhanced fermentation with A. flavus promoted an increase in the total amount of free amino acids and organic acids, particularly glutamic and acetic acids, in Douchi. A total of nine classes of compounds including esters (20), acids (11), aldehydes (12), ketones (9), alcohols (7), pyrazines (8), alkanes (10), phenols (7) and other compounds (8) were identified by gas chromatography-mass spectrometry (GC-MS). While higher levels of pyrazine and phenolic compounds were observed in naturally fermented Douchi, enhanced fermented Douchi had more acids and aldehydes. In addition, some new volatile components, such as methyl phenyl acetate and ethyl linoleate, were formed by enhanced fermentation. Electronic nose analysis revealed that the flavor of A. flavus 7622 fermented Douchi was closest to that of naturally fermented Douchi, while the largest flavor differences were found between A. flavus 7214 fermented and naturally fermented Douchi. Furthermore, A. flavus 7214-fermented Douchi had better overall flavor in sensory evaluation, mainly in terms of aroma, sourness, sweetness, and umami. To summarize, enhanced fermentation promoted the release of free amino acids, organic acids, and volatile compounds, thereby having a significant impact on sweetness, umami, and aroma. These results could provide theoretical guidance for the industrial production of Liuyang Douchi.